UPAYA MENINGKATKAN MOTIVASI MEMBACA MELALUI KEGIATAN SUPERVISI AKADEMIK STRATEGI BIBLIO TERAPI DENGAN MEMANFAATKAN PERPUSTAKAAN SEKOLAH PADA GURU DI SDN RINGINPUTIH 3 BOROBUDUR - Wahyuningsih, Endah (Information Technology Education Department, 2023)
Reality shows that the learning outcomes of social studies material Strengthening Maritime and Agricultural Economies in Indonesia is still not optimal. Indicators of the less-than-optimal role of students in learning include: many students' scores are not completed KKM; students are less active in learning in the classroom; during learning students are not orderly; students are less eager to do the task; when the discussion is dilakssiswaan interaction between students is less formed; many students complain that the material Strengthening the Maritime and Agricultural Economy in Indonesia is a saturating material. To overcome this problem, class action research (PTK) using the Cooperative Learning model was conducted. The purpose of this study was to improve the learning outcomes of students in class VIII F SMP Negeri 1 Borobudur in the 2022/2023 academic year using the STAD type Cooperative Learning model. The research subjects were 32 students, the research data sources were obtained from qualitative data in the form of data from teacher and student activity observations and quantitative data in the form of student learning outcomes test data. The results of cycle I research obtained students who were individually complete as many as 26 students with classical completeness of 81.25%. While the results of cycle II research have increased with the number of students who are individually complete as many as 30 students with a percentage of completeness of 93.75% Based on the results of this study, learning using the STAD type Cooperative Learning model can improve the learning outcomes of students in class VIII C SMP Negeri 1 Borobudur in the 2022/2023 academic year.